Biogeochemical particle flux results of drifting sediment trap systems from the northern and southern Benguela Upwelling System between 2019 and 2021 - Luisa Chiara Meiritz; Tim Rixen; Anja K van der Plas; Tarron Lamont; Niko Lahajnar (PANGAEA, 2024)
The particle flux studies were carried out by the Biogeochemistry working group at the Universität Hamburg as part of the GENUS and TRAFFIC research projects. 16 free-drifting sediment trap systems (drifters, Single Sediment Trap from Saarso/Hydrobios) were deployed during research cruises Meteor 153, Sonne 283 and Sonne 285 between 2019 and 2021. The samples were described macroscopically and microscopically and separated into size classes <1 and >1 mm and then their dry weight was determined. The main components: total carbon (Ctot), total nitrogen (Ntot) and organic carbon (Corg) were then measured using an elemental analyzer (EuroVector Euro EA 3000). Only particles <1 mm are considered as passive flux. All other sample categories are referred to as active flux.